PENATAAN KEWENANGAN PEMERINTAH DAERAH BIDANG PERTANAHAN DI MASA MENDATANG - Herry, Musleh (Fakultas Syariah, 2014)
Making a policy (regelgeving) is one of the functions of government. The fact that all citizens are always in contact with the public policy issued by governments, particularly concerning public interest. The development of the concept of state right to control the land started from the constitution which is then poured in the Agraria Law. Tenure by the State is not only done by the central government, but also by the local government through a process of devolution of authority in line with the spirit of regional autonomy laws. However, with the issuance of Government Regulation No. 38 of 2007, the fact that majority of the state's power in land still held by the central government on behalf of the state. This realitiy shows that the governenment failed to establish a decentralized system in the land sector.